'Killing is our business and business is good': The evolution of 'war managerialism' from body counts to counterinsurgency. (July 2017) - McCann, Leo
Managerialism versus professionalism is a central axis of conflict across many occupations. 'The profession of arms' is no exception. This article explores the contested yet symbiotic relationship of management and the military via a discussion of the Vietnam conflict and contemporary debates over restructuring the US military to fight so-called 'New Wars'. It portrays a complex picture of the organization and measurement of destruction, arguing that managerialism has long been an important ideological element of civilian and military practice. While management systems such as the infamous 'measurements of progress' in the Vietnam War were practically dysfunctional, they were effective up to a point in their managerialist goal of portraying civilian and military organizations as effective, evidence-based, progressive and ethical. This logic also pertains to contemporary debates over 'progress', and its measurement in the Iraq and Afghanistan counterinsurgencies and the campaign against Isil. Despite its practical limitations, managerialism is highly prevalent as ideology in warfare, fixating on tactical and operational levels, thereby excluding broader strategic, political or ethical discussions. 'Progress' and its mismeasurement in Vietnam and the New Wars are therefore best understood not simply as reasons for military and civilian failures in prolonged and inconclusive conflicts but as evidence of the success of managerialism in restricting public scrutiny and accountability of the business of war.